Effects of supplementation with lysophospholipids on performance, nutrient digestibility, and bacterial communities of beef cattle - Zhang, Meimei; Bai, Haixin; Zhao, Yufan; Wang, Ruixue; Li, Guanglei; Zhang, Yonggen; Jiao, Peixin (Frontiers in Veterinary Science, 2022)
An experiment was conducted to investigate the influences of supplemental lysophospholipids (LPL) on the growth performance, nutrient digestibility, and fecal bacterial profile, and short-chain fatty acids (SCFAs) of beef cattle. Thirty-six Angus beef cattle (565 ± 10.25 kg body weight (BW)) were grouped by BW and age, and randomly allocated to 1 of 3 treatment groups: 1) control (CON, basal diet); 2) LLPL (CON supplemented with 0.5 g/kg LPL, dry matter (DM) basis); and 3) HLPL (CON supplemented with 0.75 g/kg, DM basis). The Angus cattle were fed a total mixed ration that consisted of 25% roughage and 75% concentrate (dry matter [DM] basis). The results reveal that LPL inclusion linearly increased the average daily gain (P = 0.02) and the feed efficiency (ADG/feed intake, P = 0.02), while quadratically increasing the final weight (P = 0.02) of the beef cattle. Compared with CON, the total tract digestibilities of DM (P < 0.01), ether extract (P = 0.04) and crude protein (P < 0.01) were increased with LPL supplementation. At the phylum-level, the relative abundance of Firmicutes (P = 0.05) and ratio of Firmicutes: Bacteroidetes (P = 0.04) were linearly increased, while the relative abundances of Bacteroidetes (P = 0.04) and Proteobacteria (P < 0.01) were linearly decreased with increasing LPL inclusion. At the genus-level, the relative abundances of Clostridium (P < 0.01) and Roseburia (P < 0.01) were quadratically increased, and the relative abundances of Ruminococcus was linearly increased (P < 0.01) with LPL supplementation. Additionally, increasing the dose of LPL in diets linearly increased the molar proportion of butyrate (P < 0.01) and total SCFAs (P = 0.01) concentrations. A conclusion was drawn that, as a promising feed additive, LPL promoted growth performance and nutrient digestibility, which may be associated with the change of fecal microbiome and SCFAs.